Decision Support System (DSS) for the Determination of Percentage of Scholarship Quantity Based Fuzzy Tahani - Robby Yuli Endra; Agus Sukoco (Bandar Lampung University (UBL), 2014)
To ensure quality education, the Government must provide services and conveniences to education without any descriminations. To conduct quality education needed some big enough fee therefore for every learner at any unit of education are entitled to tuition fees for those whose parents could not afford to finance their education, and the right to obtain a scholarship for those who has achievment. (Putra & Hardiyanti, 2011).By taking the results of previous research, entitled the application of Fuzzy Inference System Mamdani's method for the determination of quantity percentage of scholarship (Research Lecturer Beginners by 2013), on research this time the researcher do application design with combination of algortitma Fuzzy Inference System Mamdani Method and using the Fuzzy Method for designing Databases Tahani decision support system (SPK).Fuzzy tahani is one method of Fuzzy that uses the database standard. the data are classified based on how the data are seen by the user. So that all the results of the algorithms of previous research can be used to create applications by using Fuzzy method Tahani Database.The type of This research is a kind of applied research, it is a bridge from basic research between experimental research. In the design and development of decision support system based on Desktop Application is a system development methodology used is a structured methodology with the model development SDLC (System Development Life Cycle) that serves to illustrate the main stages and steps of each stage are generally divided into three main activity analysis, design and implementation of data collection Techniques as well as performed there are 3 methods of interview techniques, Documentation and Observation. The Data obtained from the marketing of Computer Science Faculty -Bandar Lampung UniversityThe purpose of this research is Designing Applications by using the Fuzzy Database method's Tahani with available the desktop application so that the eligibility determination process for new student scholarships being accepted right on the target, fast and objective.